PERANCANGAN DAN PEMBUATAN SISTEM PEMASANGAN IKLAN BARIS PADA SURAT KABAR WAWASAN - DIO SEFTIAN ALIF UTAMA, 13.01.53.0029 (Information Technology and Telematics, 2017)
company advertising the advertising providers and payment transactions in cash. But with the mounting system online classified ads, ads sender does not need to go to the company and also no longer make payments in cash. System development method used in this study is a waterfall that consists of system startup, system analysis, system design using UML, system implementation using PHP and MySQL database. The end result of this research is a mounting system classified ads in newspapers Insights can be easier for customers to book ads without limitation of time and place and easy for customers to obtain information on newspaper classified ads insights quickly and easily Keywords – Classified Ads, Newspaper Insights, PHP, MySQL